Characteristics of Community Radio: An Entertainment Factory or Catalyst for Development, Food and Nutrition Security - Mac’Ouma, Enock (Current Approaches in Science and Technology Research Vol. 4, 2021)
Several studies have confirmed that Community Radio can go a long way in promoting agriculture by educating farmers about new farming methods; issuing early warning whenever there are outbreaks of pests and diseases; monitoring weather patterns and informing farmers on appropriate planting dates. Further research argues that communication of science and technology best occurs outside the school through real world experiences with the media as an important forum at which such experiences are shared. Most rural folk rely on CR as a source of news and entertainment. However, CR is much more than an entertainment factory; it is potentially an invaluable forum for rural farmers and agricultural researchers to engage in scientific dialogue, which is aimed at achieving the Sustainable Development Goal (SGD) number 2. This paper, therefore, investigates the extent to which efforts have been made to unlock CR’s potential in working towards attaining the national goal of ending hunger, achieving food security, improving nutrition and promoting sustainable agriculture. The paper will rely on survey data drawn from a recent study on the link between Community Radio and Food Security. Findings of this study indicate that Community Radio could offer a lasting solution to the challenge of rural development, especially food and nutrition security. The outcome is expected to inform policy on the need to enhance integration of CR in disseminating agricultural information to rural farmers in Kenya as the country marches towards the successful implementation of its national development goal of making Kenya a Food Secure nation.